Structured Eurobonds - Christian Bauer; Bernhard Herz; Alexandra Hild (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2011)
This paper develops a market-based approach to implement so called Eurobonds, i.e. common sovereign debt securities of European Monetary Union (EMU) countries. By applying an asset-backed security (ABS) approach positive implications of a common bond can be achieved and negative incentives (e.g. moral hazard) can be prevented. Within an ABS structure a special purpose vehicle (SPV) buys a portfolio of EMU countries debt instruments (pooling) and then issues a set of subordinated Eurobonds with varying risk and rating (tranching). By pooling and tranching the default risk is concentrated in one part of the capital structure, resulting in a large share of less risky securities and overall risk premia reduction. A fraction of the cash flows from the SPV to the countries is diverted to a trust fund, which covers the first losses in case of a country default. By contrast to propositions on Eurobonds made so far, our proposal has one major advantage: All EMU countries can benefit from participating in the ABS-structure. These benefits are driven by the following reasons: Firstly, we only introduce partial liability (10 % of initial notional) instead of joint liability in order to limit moral hazard. Secondly, interest gains are distributed among all participating and not defaulting countries. Our simulation study shows that on average all EMU member states - both high rated and low rated countries - gain by taking part in a Eurobond ABS due to the implied diversification and tranching effects. Average savings range between 8 % and 33 % of the total credit amount. Nonetheless, in the worst case scenario, there is a probability of a disprofit ranging between 5.5 % and 0 %. In our simulation Germany and Greece represent the two opposite ends of the range and therefore serve as example in the discussion.
Keywords: E6; F34; G15; 330; Eurobonds; EMU; asset-backed securities (ABS); financial instruments; indebtedness